Are suicide terrorists different from `regular militants'? - Amir Sabri; Günther G. Schulze (Public Choice, 2020)
We analyze the differences in the socioeconomic profiles between suicide terrorists and `regular' militants using a dataset of 1596 militants (including 209 suicide terrorists) from Hamas and Palestinian Islamic Jihad (PIJ). We find that suicide terrorists are better educated, younger, less likely to be married or have children, and less likely to live in the Gaza strip than their non-suicide counterparts. Moreover, although the profiles of Hamas and PIJ militants are distinctively different, the suicide terrorists are very similar to one another.
Keywords: D74; J49; Z12; 330; Suicide terrorism; Terrorism; Hamas; Palestinian Islamic Jihad